Baseline gene signatures of reactogenicity to Ebola vaccination: a machine learning approach across multiple cohorts - Gonzalez Dias Carvalho, Patrícia Conceição; Dominguez Crespo Hirata, Thiago; Mano Alves, Leandro Yukio; Moscardini, Isabelle Franco; do Nascimento, Ana Paula Barbosa; Costa-Martins, André G.; Sorgi, Sara; Harandi, Ali M.; Ferreira, Daniela M.; Vianello, Eleonora; Haks, Mariëlle C.; Ottenhoff, Tom H. M.; et al. (Frontiers in Immunology, 2023)
The rVSVΔG-ZEBOV-GP (Ervebo®) vaccine is both immunogenic and protective against Ebola. However, the vaccine can cause a broad range of transient adverse reactions, from headache to arthritis. Identifying baseline reactogenicity signatures can advance personalized vaccinology and increase our understanding of the molecular factors associated with such adverse events. In this study, we developed a machine learning approach to integrate pre-vaccination gene expression data with adverse events that occurred within 14 days post-vaccination. We analyzed the expression of 144 genes across 343 blood samples collected from participants of 4 phase I clinical trial cohorts: Switzerland, USA, Gabon, and Kenya. Our machine learning approach revealed 22 key genes associated with adverse events such as local reactions, fatigue, headache, myalgia, fever, chills, arthralgia, nausea, and arthritis, providing insights into potential biological mechanisms linked to vaccine reactogenicity.